A rare case of subglottic ectopic thyroid tissue causing upper airway obstruction: detection by CECT and MRI neck - Ngah, Nur Aimi; Muhammad, Siti Jusna @ Siti Sharifah; Mohamad Saini, Suraini; Md Noh, Mohamad Syafeeq Faeez; Ab. Hamid, Suzana; Salleh, Hisyam; Suppiah, Subapriya (Universiti Putra Malaysia Press, 2018)
Internal obstruction of the upper airways can be due to infection, anaphylactic reaction, congenital anomaly, foreign body inhalation or mass. This case report is of a lady who presented with upper airway obstruction due to subglottic ectopic thyroid tissue. She had a history of noisy breathing and progressive neck swelling since childhood. Biochemical results showed hypothyroid features while flexible scope showed tracheal stenosis. Computed Tomography (CT) detected a goitre and a posterior laryngeal mass at subglottic region causing laryngeal stenosis. The MRI helped to better delineate the soft tissue details of this mass. while elective direct laryngoscope showed a firm mass arising from the trachea. Debulking of the mass was done and histopathological diagnosis was nodular thyroid hyperplasia. Treatment with L-thyroxine was instituted with good clinical improvement. An ectopic thyroid gland can develop if its normal migration is halted along this tract during embryogenesis. Subglottic location of ectopic thyroid is extremely rare. However, ectopic thyroid tissue in the larynx should be considered as a possible diagnosis causing upper airway obstruction, especially in a patient that is clinically hypothyroid and having a concurrent goitre.